The implementation of students’ co-curricular activities and its method of development at Buraydah College, Saudi Arabia: An analysis / Abdulrahman Saleh O Alshetaiwi - Abdulrahman Saleh O, Alshetaiwi (2017)
The current study aims at recognizing the reality of the extracurricular students’ activities, its barriers, and methods of development in Buraydah National Colleges, and to identify the extent of the differences between the averages of students' estimates and teaching staff according the Variables of gender, the College and the specialties (Literary / Scientific) towards the extracurricular students’ activities, its barriers, and its methods of developing. The Researcher used the descriptive analytical method as he prepared a questionnaire that consisted of three areas, with a total number of (66) paragraphs. Study community was from all the students and teaching staff in Buraidah National colleges as the random sample was chosen from the original community and its number was (600) members distributed as follow: (450) students, and (150) from the teaching staff, data were statically processed by the use of the SPSS Program. The study reached to the following findings: - The reality of the of the extracurricular students’ activities in Buraydah National colleges was good according to the sample individuals’ point of views. - There were a group of barriers like (the administrative, the organizational, the environmental, the community, the materialistic, and the humanitarian) that confronted the practice of the extracurricular students’ activities in Buraydah colleges, where the environmental and community barriers were the most prominent barriers that faced the extracurricular students’ activities. - There are no significant statistical differences at the significance level (α ≤ 0.05) between the Arithmetic averages for the students’ estimates towards the reality of the extracurricular students’ activities, its barriers and methods of developing that are ascribed to the two variances of gender and specialties (Literary / Scientific). - There are no statistical significant differences at the significance level (α ≤ 0.05) between the Arithmetic averages for the teaching staff towards the extracurricular students’ activities reality, its barriers, and methods of developing that are ascribed to the two variances of gender and the college, where as there are differences between them all towards planning for the extracurricular students’ activities, and the human barriers that are ascribed to specialties ((Literary / scientific) for the favor of the literary specialties. - There are no statistical significant differences at the significance level (α ≤ 0.05) between the Arithmetic averages for the teaching staff and students’ responses towards the reality of the extracurricular students’ activities, its barriers (the materialistic, the environmental, the community and the humanitarian) and its methods to develop for the favor of the teaching staff. - There are no significant statistical differences at the significance level (α ≤ 0.05) between the Arithmetic averages for the students’ responses towards the extracurricular students’ activities and methods of developing that is ascribed to the variance of college, whereas there are differences towards the barriers of the extracurricular activities. The study reached to a group of recommendations, the most important, is the necessity of removing the obstacles, for which the individuals of the study sample agreed upon, continuous correction for the extracurricular students’ activities, providing awards, financial and material incentives for the participants in the activities, reducing the burden on the teaching staff who supervise the activities, and Providing resources and potentials needed to diversify the extracurricular students’ activities.